Optimizing the sensing performance of a single-rod fluxgate magnetometer using thin magnetic wires. (12th October 2015) - Can, Hava; Svec, Peter; Tanrıseven, Sercan; Bydzovsky, Jan; Birlikseven, Cengiz; Sözeri, Hüseyin; Svec, Peter; Topal, Uğur
Abstract: This paper presents the optimal conditions for the design of a single-rod fluxgate magnetometer using Co-based amorphous magnetic wires with reduced geometrical dimensions of 100 μ m in diameter. In order to enhance the performance of the current sensor (i.e. the noise level, the sensitivity, the dynamical range, the scaling factor, etc), the core materials were subjected to annealing at different annealing temperatures in a longitudinal magnetic field ranging from 0 to 0.5 T. The B – H measurements have shown that the heat treatments significantly change the magnetic parameters of the cores (the saturation field, the initial and apparent permeabilities). For instance, the initial permeability μ i attains values of between 3500 and 4700 depending on the treatment conditions. These magnetic parameters were subsequently correlated with the sensor performance by using the principles of the fluxgate physics. Consequently, the enhanced fluxgate effect with improved sensing characteristics has been obtained by annealing the wire core at 250 °C ( B = 0 T). It is shown that this magnetic wire with a sensing area of 0.00785 mm 2 is suitable as a sensor core for the nondestructive testing of metallic objects and the surfaces of magnetic cards. The sensor signal shows perfect linear dependence to dc or low frequency fields up to 1 Oe. The fitting parameters R 2 of 0.9998 could be achieved in a dc field interval of −1.0 Oe and 1.0 Oe (when R 2 =1.0, all points lie exactly on the curve with no scatter). Such linearity has not been seen in such a large dynamical range until now in the rod-type single-core fluxgates. It is also shown that there is no hysteresis on the V 2 f – H dc graphs (the V 2 f is the sensor signal) even after applying fields as high as 100 Oe. Besides, the cross-field effect is almost zero due to the geometry of the long-thin wire.